2019
DOI: 10.1093/nar/gkz177
|View full text |Cite
|
Sign up to set email alerts
|

Translation termination depends on the sequential ribosomal entry of eRF1 and eRF3

Abstract: Translation termination requires eRF1 and eRF3 for polypeptide- and tRNA-release on stop codons. Additionally, Dbp5/DDX19 and Rli1/ABCE1 are required; however, their function in this process is currently unknown. Using a combination of in vivo and in vitro experiments, we show that they regulate a stepwise assembly of the termination complex. Rli1 and eRF3-GDP associate with the ribosome first. Subsequently, Dbp5-ATP delivers eRF1 to the stop codon and in this way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…This data shows that the presence of GFP did not contribute to the nuclear localization of Dbp5 L12A . Given the strong nuclear localization of Dbp5 L12A , plus the previous reports of Dbp5 functioning in translation control (Beißel et al, 2019; Bolger et al, 2008; Gross et al, 2007), the overall fitness of a strain carrying an untagged and integrated allele of dbp5-L12A raises questions as to the requirements for Dbp5 in the cytoplasm, which this allele could be used to address.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This data shows that the presence of GFP did not contribute to the nuclear localization of Dbp5 L12A . Given the strong nuclear localization of Dbp5 L12A , plus the previous reports of Dbp5 functioning in translation control (Beißel et al, 2019; Bolger et al, 2008; Gross et al, 2007), the overall fitness of a strain carrying an untagged and integrated allele of dbp5-L12A raises questions as to the requirements for Dbp5 in the cytoplasm, which this allele could be used to address.…”
Section: Resultsmentioning
confidence: 99%
“…Several additional roles for Dbp5 in gene expression have been proposed that point to functions of Dbp5 in the nuclear and cytoplasmic compartments. For example, studies have shown both physical and genetic interactions between Dbp5 and transcription initiation and translation termination machinery (Alcázar-Román et al, 2010; Beißel et al, 2019; Bolger et al, 2008; Estruch et al, 2012; Estruch and Cole, 2003; Gross et al, 2007). Additionally, a role for Dbp5 in the nuclear export of pre-ribosomal subunits has been identified (Neumann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…eIF3 has been reported to increase TR by interfering with eRF1 decoding of stop codon at the third/wobble position (Beznoskova et al, 2015). Rli1/ABCE1 facilitates recruitment of eRFs to the ribosome and promotes termination (Beissel et al, 2019; Shoemaker and Green, 2011). Dbp5/DDX19 stabilizes termination complex and prevents premature dissociation of eRFs (Beissel et al, 2019; Mikhailova et al, 2017), while Gle1 functions together with Dbp5 to regulate termination (Bolger et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…HBS1L, also known as eRF3c, encodes protein belongs to eRF3 family member which has multifunctional properties including translation termination [25], mRNA decay [26] etc. It's reported that Polyglycine expansions in eRF3 regulating its expression and/or changing the protein function are associated with gastric cancer susceptibility [27].…”
Section: Discussionmentioning
confidence: 99%